Assessing Dendrochronological Potential of Escallonia myrtilloides in the High Andes of Peru - Requena-Rojas E.J. (2021)
The authors thank Rosana Ordaya and Johan Lázaro for their help in the field, Ricardo Rodríguez and Luiz Santin for the histological cuts, and Wil-fredo Bulege for the administrative support of the project. We also thank two anonymous reviewers for their valuable comments and Anabela Bonada for the writing and language editing. This study was financed by the National Council for Science, Technology and Technological Innovation-Peru (Project N° 147-2015-FONDECYT-DE, Project N° 039-2019-FONDECYT-BM-INC-INV).